2010
DOI: 10.1111/j.1540-6261.2010.01614.x
|View full text |Cite
|
Sign up to set email alerts
|

Who Blows the Whistle on Corporate Fraud?

Abstract: To identify the most effective mechanisms for detecting corporate fraud, we study all reported fraud cases in large U.S. companies between 1996 and 2004. We find that fraud detection does not rely on standard corporate governance actors (investors, SEC, and auditors), but rather takes a village, including several nontraditional players (employees, media, and industry regulators). Differences in access to information, as well as monetary and reputational incentives, help to explain this pattern. In-depth analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
771
3
11

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,454 publications
(809 citation statements)
references
References 44 publications
24
771
3
11
Order By: Relevance
“…Analysts perform a monitoring role in firms' financial reporting processes [23,25,43,44]. In fact, Yu (2008) [23] and Yoo et al (2012) [44] confirmed that the discretionary accruals decrease more in firms with many analysts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Analysts perform a monitoring role in firms' financial reporting processes [23,25,43,44]. In fact, Yu (2008) [23] and Yoo et al (2012) [44] confirmed that the discretionary accruals decrease more in firms with many analysts.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent researchers have shown that the disclosure of information through analysts' forecast activities can improve the quality of financial reporting. Dyck et al (2010) [43] reported that analysts (16.9%) are more likely to detect fraudulent cases of firms than external auditors (11.3%). Yu (2008) [23] and Yoo et al (2012) [44] confirmed that analysts' coverage affects earnings management through accruals, and that discretionary accruals are reduced more in firms with more analyst coverage.…”
Section: Analysts' Coverage Seo and Investment Efficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…If there are too many exclusions, then individuals may be reluctant to risk coming forward. Recent research (Dyck et al 2010) suggests that employees have low costs to accessing information, but monetary incentives are needed to overcome the risks of coming forward.…”
Section: Responses To Specific Questionsmentioning
confidence: 99%